Customs Affairs - Zelinska, Olena Z. (Lesya Ukrainka Volyn National University, 2024)
The theoretical foundations of the country's customs affairs will be studied, its organization at the current stage, the structure of subjects and administrative institutions of customs activities, their tasks and functions, international and domestic regulatory and legal foundations of customs management, the features of customs control regulation and its impact on international trade and the national economy; processes of customs clearance, customs procedures, customs tariffs, as well as the analysis of international trade agreements; practical skills in customs control and customs clearance, etc. will be acquired.
Keywords: Country's Customs System Functioning; Special Customs Procedures